Respuesta :
Answer:
Step-by-step explanation:
y = 4x – 17..........(1)
3x + y = 4............(2)
Substituting y = 4x - 17 in (2)
3x + 4x - 17 = 4
7x = 4 + 17
7x = 21
x = 21/7
x = 3
Putting x = 3 in equation (1)
y = 4x - 17
y = 4(1) - 17
y = 4 - 17
y = -13
Hey! :)
First, let us learn about substitution.
Let's say we have an equation 3x + 1y = 1 and 1x + 2y = 6
You need to pick one equation to solve for x.
Let's say we picked 1x + 2y = 6 for x to solve for y.
Then you'd solve.
Now onto the equation.
- Substitute 4x−17 for y in 3x+y=4:
3x+y=4
3x+4x−17=4
7x−17=4 - Simplify both sides.
7x−17+17=4+17 Let's add 17 to both sides.
7x=21
Divide both sides by 7.
7x/7 = 21/7
x = 3
Hope you had a great experience on Brainly!